Epizoothological, clinical features and control measures of American foulbrood in the world (literature review) - M. S. Karpulenko; Yu. G. Storchak; V. O. Postoienko; L. Y. Kornienko; M. M. Babkina; G. V. Kyivska; V. V. Kulykova; L. V. Togachynska; O. V. Matviienko; O. O. Pyskun; T. M. Ukhovska (One Health Journal, 2026)
The article summarizes and analyzes modern scientific data on the epizootological and clinical features of American foulbrood (AFB) of bees, the causative agent of which is the spore-forming bacterium Paenibacillus larvae. The historical aspects of the study of the disease, the biological properties of the pathogen, itʼs high resistance in the environment and the ability to maintain infectivity for a long time are highlighted. The ERIC I–V genotypes, their prevalence and differences in virulence are characterized. Based on WOAH (WAHIS) and ProMED data, the modern epizootic situation in the countries of Europe, Asia, Africa and America is analyzed, which indicates the global spread of the disease and its significant economic impact on the beekeeping industry. Typical clinical signs of AFB are described, in particular, variegation of brood, sunken cell lids, the presence of a viscous putrefactive mass and the formation of dense scales. Modern approaches to laboratory diagnostics are considered, including microscopic, bacteriological and molecular genetic methods with an emphasis on the high sensitivity of PCR for early detection of the pathogen. The main preventive measures are summarized, which include compliance with veterinary and sanitary standards, regular monitoring of apiaries, control of bee movements and timely elimination of dysfunctional colonies, which are key to preventing the spread of American foulbrood.